KARAKTERISTIK TEPUNG DAUN KELOR BERDASARKAN PERBEDAAN SUHU DAN LAMA BLANSING - Dewi, Ni Putu Satya Kencana; Wisaniyasa, Ni Wayan; Wartini, Ni Made (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2023)
Moringa plants contain various types of bioactive compounds in the form of phenolic compounds as antioxidants that are beneficial for health. One way of processing moringa leaves is to make moringa leaf flour by drying and blanching methods. The purpose of this study was to determine the effect of the best blanching time and temperature to produce moringa leaf flour. The blanching of moringa leaf flour was conducted with temperatures of 80 ± 2oC, 90 ± 2oC, and 100 ± 2oC and a duration of 5 minutes, 7 minutes, and 9 minutes. Based on the results, the variance of temperature and duration of blanching significantly affected the yield, total phenol content, beta-carotene content, and antioxidant activity (IC50) of moringa leaf flour. The results of the effectiveness index test showed that treatment at a temperature of 90 ± 2oC and a duration of 5 minutes produced the best moringa leaf flour with yield characteristics of 24.44 ± 0.09%, total phenol content 666.89 ± 4.57 mg/100 g, beta-carotene content 5763.86 ± 3.03 mg/100 g and antioxidant activity (IC50) 840.49 ± 31.29 ppm.